БООЛЫН БООЛ ГЭЖ ХЭН БЭ? - Л.Одзаяа (Acta Mongolica, 2013)
In the Data article clarified the questions of the subordination of Tannu Tuva, and the history of their area, reviewed the history in which the Qing Empire invaded and took them in his chain of command.